Determinants Of Public Procurement Corruption In Uganda: A Conceptual Framework - Basheka, Benon C.; Tumutegyereize, Milton (Journal of Public Procurement, 2011)
This paper examines the determinants of public procurement corruption in Uganda using factor analysis and multiple correlation analysis. In this study, the economic, political, organizational and social determinants were found to have a statistically significant relationship with public procurement corruption. However, the paper concludes that organizational determinants are the major factors, which account for the increasing trends of procurement corruption. Efforts at minimizing public procurement corruption must therefore target the identified organizational opportunities at both central and local government levels, which perpetuate the problem of corruption.
Keywords: Corruption, Procurement, Procurement corruption and Service Delivery